Servicio tutorial participativo y satisfacción con el servicio educativo en los padres de familia de la Institución Educativa Inicial Bilingüe Intercultural N° 386 Bellavista Callarú, Loreto 2023 - Coello Suarez, Sindi Adriana (2024)
The research conducted at the Bilingual Intercultural Initial Educational Institution No. 386 Bellavista Callarú Loreto during the year 2023 provides empirical evidence on the relationship between participatory tutorial service and satisfaction with the educational service in said institution. Through a non-experimental, field, bivariate, and cross-sectional research design of a relational nature, this study analyzed the perceptions of 62 parents, constituting both the population and the sample of the study. For data collection, questionnaires were designed and validated, applied through the survey technique. The results reveal a significant and positive moderate degree correlation between the participatory tutorial service and satisfaction with the educational service, with a rho correlation coefficient of .633 and a p-value of .000. These findings allow for the rejection of the null hypothesis and the acceptance of the alternative hypothesis, confirming the existence of a direct relationship between the quality of the participatory tutorial service and the level of satisfaction of the parents. This link underscores the need to implement and maintain high standards in participatory tutorial services as a strategy to enhance a positive perception of the educational service among the parent community. The findings suggest that educational policies and practices should focus on strengthening collaboration between parents and educators, promoting strategies that allow for greater parental involvement in the academic and formative accompaniment of their children.